Basic parameters in speech processing. The need for evaluation - HÖGE, Harald (Archives of Acoustics, 2007)
As basic parameters in speech processing we regard pitch, duration, intensity, voice quality, signal to noise ratio, voice activity detection and strength of Lombard effect. Taking in account also adverse conditions the performance of many published algorithms to extract those parameters from the speech signal automatically is not known. A framework based on competitive evaluation is proposed to push algorithmic research and to make progress comparable.